Analysis of Operating Capacity of SF Holding Co., Ltd. - Liangyu Chen (Journal of Frontier in Economic and Management Research, 2025)
Currently, China's express delivery industry is developing rapidly and has become an important part of modern service industry. However, the industry faces challenges such as a large market scale but high fragmentation and low concentration. For express delivery enterprises to achieve development, they should focus on improving their operating capacity. As a leading enterprise in China's express delivery industry, SF Holding Co., Ltd. (hereinafter referred to as "SF Holding") embodies both industry-wide commonalities and unique characteristics, thus having high research value. This paper aims to analyze the operating capacity of SF Holding by examining its operating indicators disclosed from 2019 to 2023 and comparing them with peer enterprises. It identifies issues in SF Holding's operating capacity, including excessive accounts receivable, inventory backlogs, and low total asset turnover. Corresponding improvement suggestions are proposed: improving credit systems, strengthening inventory management, and rationalizing asset allocation. It is hoped that this study can effectively help SF Holding optimize its operating capacity, enhance market competitiveness, and provide references for other enterprises in the express delivery industry to promote sustainable and collective development of the industry.